Evaluation of long lasting insecticidal nets in experimental huts and WHO PQT/VCP compliance: A systematic review - Divya Teja Koppula; Ananganallur Nagarajan Shriram; Amala Ramasamy; Ashwani Kumar; Manju Rahi (PLoS ONE, 2025)
Malaria control in highly endemic regions relies heavily on vector control tools, particularly LLINs. The effectiveness of LLINs varies by eco-epidemiological conditions and brands. A comprehensive review of WHO interim-approved LLIN brands is necessary to address this variability. This systematic review screened 145 articles, refining them to 27 eligible publications, to assess the efficacy of WHO-recommended LLINs, focusing on synthetic pyrethroids and synergists like Piperonyl Butoxide or Pyriproxyfen. The review demonstrated that LLINs impregnated with synthetic pyrethroids, especially when used with synergists, are more effective than regular LLINs. However, adherence to WHO PQT/VCP (World Health Organization Prequalification Unit/Vector Control Product) checklists was inconsistent. Several LLIN pairs which includes candidate and comparator nets showed equal efficacy (100% in both arms), including Olyset Plus vs. Olyset Net, DuraNet vs. PermaNet 3.0, Interceptor G2 vs. Interceptor, MagNet vs. DuraNet, Dawa Plus 3.0 vs. Dawa Plus 2.0, and Veerralin vs. PermaNet 3.0 in terms of mosquito mortality. Significant efficacy differences were noted between various bed net pairs: Interceptor vs CTN (RR: 1.5, 95% CI: 1.28-1.66); Olyset Net Duo vs Olyset Net (RR: 1.1, 95% CI: 1.01-1.18); ICON Maxx vs CTN polyester (RR: 7.7, 95% CI: 3.6-16.31); Dawa Plus 3.0 vs Dawa Plus 2.0 (RR: 2.1, 95% CI: 1.34-3.15); Interceptor G2 vs Interceptor G1 (RR: 0.9, 95% CI: 0.77-0.96). These findings inform the development of improved net designs and ensure alignment with WHO guidelines, enhancing vector control measures. The review supports improved malaria control strategies and sustained LLIN utilization, highlighting the need for LLIN manufacturers to align with WHO guidelines.